2020
DOI: 10.21037/tlcr-20-679
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant genetic alterations are associated with response to EGFR targeted therapy in patients with lung adenocarcinoma

Abstract: Background: Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are considered to be more effective than chemotherapy in the treatment of EGFR-mutant advanced non-small cell lung cancer (NSCLC). However, in addition to EGFR-sensitive mutations, the genetic factors that affect the prognosis of patients who receive TKI treatment are not yet clear. Methods: The clinical data of 36 NSCLC patients with EGFR mutation who received TKI treatment were retrospectively analyzed. Liquid re-biopsy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Though seldom previous research explored the clinical implications of concomitant mutations from multiple pathways in HER2-related signaling network for breast cancer, several previous studies [ 21 25 ] in EGFR-mutant advanced non-small cell lung cancer investigated the relationship between concomitant genetic alterations and survival outcomes. The results based on updated data in this analysis is consistent with previous studies [ 21 25 ], suggesting that significant concomitant genetic mutations may play a key role in drug resistance and tumor progression, and may be a significant factor affecting clinical survival outcomes [ 24 ]. Besides that, significantly shorter PFS was observed in the patients with PIK3CA mutation and ERBB2 mutation via the biomarker analysis of ctDNA when compared to those of wide type in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Though seldom previous research explored the clinical implications of concomitant mutations from multiple pathways in HER2-related signaling network for breast cancer, several previous studies [ 21 25 ] in EGFR-mutant advanced non-small cell lung cancer investigated the relationship between concomitant genetic alterations and survival outcomes. The results based on updated data in this analysis is consistent with previous studies [ 21 25 ], suggesting that significant concomitant genetic mutations may play a key role in drug resistance and tumor progression, and may be a significant factor affecting clinical survival outcomes [ 24 ]. Besides that, significantly shorter PFS was observed in the patients with PIK3CA mutation and ERBB2 mutation via the biomarker analysis of ctDNA when compared to those of wide type in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Their results showed that TP53 mutations were independently associated with worse outcomes in cohort 1, while in cohort 2, TP53 , RB1 , and PTEN mutations as well as MDM2 amplifications all resulted in shorter PFS ( 11 ), suggesting that concurrent genomic alterations accelerated the resistance to EGFR TKIs. Additionally, co-occurring TP53 mutations were reported to be associated with worse outcomes of EGFR TKIs in several studies ( 10 , 11 , 13 , 32 ). However, these concomitant genetic alterations in previous studies were mostly considered untargetable without available drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Several studies have indicated that concomitant EGFR mutations affect the prognosis of patients with cancer. Chen et al [46] found that patients with concomitant mutations had significantly lower ORR (43.8 vs. 80.0%; P = 0.02) and PFS (P < 0.01) than those without concomitant mutations, after receiving EGFR-TKI treatment. In the BENEFIT phase 2 clinical trial, among patients with EFGR mutations, patients with single EGFR mutations had a better prognosis than patients with concomitant tumor suppressor gene mutations and concomitant oncogene mutations, with a median PFS duration of 13.2 (95% CI: 11.5-15.0) months, 9.3 (95% CI: 7.6-11.0) months, and 4.7 (95% CI: 1.9-9.3) months, respectively.…”
Section: Egfr Concomitant Mutationsmentioning
confidence: 99%